1995
DOI: 10.1177/0022022195261003
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Differences and Cross-Cultural Similarities in Appraisals and Emotional Responses

Abstract: To conduct a cross-cultural test of a theory specifying the appraisals that elicit particular emotions, undergraduates from India and the United States were asked how they appraised events that caused them to feel sadness, fear, or anger. In both cultures there was evidence that an appraisal of powerlessness characterized incidents leading to sadness and fear, rather than anger; and an appraisal that other persons caused negative events characterized incidents leading to anger, rather than sadness or fear. Als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Second, our findings have tapped into an interesting issue for cross-cultural studies on emotion. Although culture is becoming an increasingly important variable in mainstream emotion research (e.g., Kitayama & Markus, 1994;Russell, FernandezDols, Manstead, & Wellenkamp, 1995), much of the attention has been centered on the structural similarity or difference of emotional experience across cultures (e.g., Mauro, Sato, & Tucker, 1992;Mesquita & Frijda, 1992;Roseman, Dhawan, Rettek, Naidu, & Thapa, 1995;Russell, 1991;Scherer & Wallbott, 1994). Along with the question of whether different cultural members are alike or different in their affective reactions to various antecedent conditions of emotion, our findings suggest that the functional value or significance attached to such affective experience may differ across cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our findings have tapped into an interesting issue for cross-cultural studies on emotion. Although culture is becoming an increasingly important variable in mainstream emotion research (e.g., Kitayama & Markus, 1994;Russell, FernandezDols, Manstead, & Wellenkamp, 1995), much of the attention has been centered on the structural similarity or difference of emotional experience across cultures (e.g., Mauro, Sato, & Tucker, 1992;Mesquita & Frijda, 1992;Roseman, Dhawan, Rettek, Naidu, & Thapa, 1995;Russell, 1991;Scherer & Wallbott, 1994). Along with the question of whether different cultural members are alike or different in their affective reactions to various antecedent conditions of emotion, our findings suggest that the functional value or significance attached to such affective experience may differ across cultures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cultures differ in terms of appraisals that lead to emotion (Matsumoto, Kudoh, Scherer & Wallbot, 1988;Mauro, Sato & Tucker , 1992;Roseman, Dhawan, Rettek & Naidu, 1995;Scherer, 1997aScherer, , 1997b, emotional expression (Matsumoto & Kupperbusch, 2001), and coping (Bjorck, Cuthbertson, Thuman & Lee , 2001;Cole, Bruschi & Tamang, 2002;Hwang, Scherer, Wu, Hwang & Li , 2002;Morling, Kitayama & Miyamoto, 2003;Taylor, Sherman, Kim, Jarcho & Takagi, 2004;Tweed, White & Lehman et al, 2004;VanderVoort, 2001;Yeh & Inose, 2002). According to the most recent empirical findings, however, such cultural differences in ER are mostly accounted for by individual differences in personality traits.…”
Section: Studymentioning
confidence: 99%
“…For example, cultures differ in appraisals that lead to emotion Mauro, Sato, & Tucker, 1992;Roseman, Dhawan, Rettek, & Naidu, 1995;Scherer, 1997aScherer, , 1997b, and these might correspond with situation selection. Cultures differ in emotional expression (Ekman, 1972;Friesen, 1972;Matsumoto & Kupperbusch, 2001) and in the rules governing their modification called display rules (Biehl, Matsumoto, & Kasri, in press;Matsumoto, 1990Matsumoto, , 1993Matsumoto, Takeuchi, Andayani, Kouznetsova, & Krupp, 1998;Matsumoto et al, 2005b;Matsumoto, Yoo, Hirayama, & Petrova, 2005c).…”
Section: Previous Research Documenting Cultural Differences In Emotiomentioning
confidence: 99%